The Discovery of Rapid Polarization Angle Variation during the 2022 Outburst of XTE J1701-462 - Qing-Chang Zhao; Hong Li; Lian Tao; Hua Feng (The Astrophysical Journal)
The geometry of the Comptonization corona in neutron star low-mass X-ray binaries is still unclear. We conducted time-resolved polarimetric analysis of the archival observations of XTE J1701–462 obtained with the Imaging X-ray Polarimeter Explorer during its 2022 outburst and found that the polarization angle (PA) varied significantly with time when the source was in the normal branch, with 67 ^∘  ± 8 ^∘ in the first epoch, −34 ^∘  ± 8 ^∘ in the second, and −58 ^∘  ± 8 ^∘ in the third, last epoch. Meanwhile, the polarization degree remained constant at around 2%, above the minimum detectable polarization at the 99% confidence level (MDP _99 ). The rapid PA variation causes depolarization in the time-averaged data, resulting in a nondetection as reported in the literature. The rapid (intraday) PA variation may suggest that there is a fast transformation of the corona geometry, likely switching from a slab geometry with enhanced disk emission and reflection, to a more vertically extended spreading layer geometry.